Analysis of the Impact of PPKM on MSMEs Income (Micro, Small and Medium Enterprises) case study Wonosari Barat Village, Bengkalis Regency Riau Province - Zulfikar Hasan; Reno Firdaus; Dinda Sri Dewi Lestari (Sanskara Manajemen Dan Bisnis, 2022)
This study examines the impact of COVID-19 on MSME business income in West Wonosari Village, Bengkalis Regency. This study aims to determine the impact of the COVID-19 pandemic on the economic situation in the community, especially small and medium enterprises (SMEs) in West Wonosari Village. The data collection process was carried out by conducting documentation and interviews with several traders who were selling around the village of West Wonosari, such as vegetable traders, fruit traders, staple food traders and others, totaling 12 respondents. This research used a qualitative descriptive method. The results of the study show that the impact caused by the Covid-19 pandemic is the level of people's purchasing power decreases and the market situation becomes quiet. Of the 12 traders studied, it had such a big impact on MSMEs, sales decreased drastically. The average decline in income for all businesses was 73.6%, from income before Covid-19.